Timor-Leste Economic Report, March 2018 - World Bank Group (World Bank, Washington, DC, 2018)
Gross domestic product (GDP)1 growth is expected to have fallen sharply in 2017 to a projected -1.8 percent from 5.3 percent the year before. This contraction is driven by a reversal of trend in government spending. In the last six months, the political impasse has worsened, with the President declaring a ‘serious institutional crisis’ and dissolving Parliament in January 2018. The current government has not been able to pass its rectification budget for 2017 nor a budget for 2018 to date. The resulting tight budget envelope has led to a sharp reduction in government expenditure of some 24 percent year-on-year, especially felt in the last three months of the year. With government expenditure making up about 75 percent of GDP, weakening expenditure has had a significant downwards impact on growth in 2017. Offshore petroleum production has continued to gradually decline over 2017 as existing fields are steadily depleted, while coffee exports were lower in 2017 due to poor weather conditions. International arrivals by air continued to grow, suggesting that the international visitor market has held up. Private consumption has been more robust in 2017, but investment, both public and private, has declined and foreign direct investment (FDI) has dried up. There remains an urgent long-term agenda of development in Timor-Leste which a new government program could focus on. Key priority reform areas include addressing the multi-sectoral challenge of severe malnutrition, improving systems of public service delivery, supporting a broadening and diversification of the economy, and putting environmental and fiscal management back on a sustainable path. Existing fiscal reserves provide a golden opportunity to achieve these reforms, but only if they are utilized to support a transition to a long-term sustainable economic and fiscal model.